ECA-based interoperability framework for intelligent building - Perumal, Thinagaran; Sulaiman, Md Nasir; Leong, Chui Yew (Elsevier, 2013)
The field of intelligent building includes a variety of systems with high level of heterogeneity. Recent advancements in sensor technologies and industrial electronics have increased the growth of heterogeneous systems in building environment. Many of these heterogeneous systems are disparate and not intended to perform mutual interoperation. Hence, it is rather difficult to execute interoperation especially in achieving desired services preferred by building owners and occupants. Complexity of interoperation is one the main reason for ambiguity in interoperability among heterogeneous systems in intelligent building. In intelligent building, an unrestricted joint execution of tasks between heterogeneous systems is essential to offer services that meet the building occupants’ requirements. In this paper, we present an Event-Condition-Action (ECA) based interoperability framework for intelligent building management by providing decision support ability among heterogeneous systems. The framework is interwoven with Web Services to provide unified integration among heterogeneous systems. The framework has been implemented with several systems to demonstrate their efficiency for joint interoperation. The framework was tested in Ethernet environment and proved to be reliable in intelligent building setting.